RADIAL VELOCITIES OF SUPERGIANTS STARS AROUND THE H AND X PERSEI CLUSTER - MENDOZA, EUGENIO; CHAVIRA, E (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1953)
Radial velocities of seven supergiant early-type stars probable members of the h and X Persei cluster have been derived from spectrograms taken at the Mc Donald Observatory. The possibility to verify with these velocities and eighteen other obtained from
BOL OBS TONAN TACUB
Keywords: RADIAL VELOCITIES, SUPERGIANTS, STARS, AROUND, H, X, PERSEI CLUSTER; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS